Psychological stress of general practitioners in the care of patients with palliative care needs: an exploratory study - Lopez, Verena; van der Keylen, Piet; Kühlein, Thomas; Sebastiao, Maria (BMC Palliative Care, 2024)
Background: In Germany, general practitioners play a pivotal role in palliative care provision. Caring for patients with palliative care needs can be a burden for general practitioners, highlighting the importance of self-care and mental health support. This study aimed to explore the role of palliative care in general practitioners’ daily work, the stressors they experience, their coping mechanisms, and the potential benefits of Advance Care Planning in this context. Methods: An exploratory approach was employed, combining a short quantitative survey with qualitative interviews. The analysis was based on a structuring qualitative content analysis, following a deductive-inductive procedure and integrating the Stress-Strain Model and Lazarus’ Transactional Model of Stress and Coping. We recruited eleven general practitioners to take part in the study. Results: General practitioners viewed palliative care as integral to their practice but faced challenges such as time constraints and perceived expertise gaps. Societal taboos often hindered conversations on the topic of death. Most general practitioners waited for their patients to initiate the topic. Some general practitioners viewed aspects of palliative care as potentially distressing. They used problem-focused (avoiding negative stressors, structuring their daily schedules) and emotion-focused (discussions with colleagues) coping strategies. Still, general practitioners indicated a desire for specific psychological support options. Advance Care Planning, though relatively unfamiliar, was acknowledged as valuable for end-of-life conversations. Conclusions: Palliative care can be associated with negative psychological stress for general practitioners, often coming from external factors. Despite individual coping strategies in place, it is advisable to explore concepts for professional psychological relief. Trial registration: Not registered.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Advance care planning; Burden; Coping mechanism; Emotional; General practitioner; Palliative care; Stress; Stressor